MARKETING AND INNOVATION STRATEGIES USED BY COCOA LAND BALI TO MAINTAIN CONSUMER BUYING INTENTIONS - Pika, Putu Ayu Titha Paramita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
In order to satisfy their demands and needs, the marketing strategy is willing to spend what is required. Cocoa Land Bali is a popular destination for classic chocolate souvenirs in Tabanan. To keep up with advances, marketing firms must be able to see opportunities or be sensitive to current ones in order to generate creativity and new achievements. This study was carried out at Cocoa Land Bali, which can be found at Jalan Raya Denpasar Bedugul, Mekarsari, District Baturiti, Tabanan Regency. The informants in this study were Cocoa Land Bali's leadership and personnel, as well as visitors who were photographed utilizing purposeful procedures. In this study, data was gathered through interviews, observation, and documentation. The validity of the data in this study is tested using triangulation of sources and procedures. In this study, data analysis includes data reduction, data display, and generating conclusions. The results show that there are four ways for businesses to keep customers coming back: coming up with new ways to do business, using good marketing strategies, being competitive in how you do business, and making sure you meet customers' needs through focused buying programs